Assessing Pulmonary Function Tests in Patients with Thalassemia Major: A Descriptive Cross-Sectional Study - Alireza Shafiei; Mohammad kajiyazdi; Mohammadali Ehsani; Elham Shahgholi; Saman Aghabekloo (Golestan University Of Medical Sciences, 2022)
Background and objectives: Major β-thalassemia refers to a severe form of β-thalassemia in which, patients need blood transfusions from an early age. Iron overload is an important and long-term complication of repeated blood transfusions. The lungs are one of the sites of iron deposition; therefore, it is essential to investigate lung dysfunction due to iron deposition. This study evaluates pulmonary function tests in β-thalassemia major patients receiving regular blood transfusions and chelation therapy. Methods: In this cross-sectional descriptive study, 120 patients (68 males and 52 females) with β-thalassemia major aged 6 to 41 years who underwent blood transfusion at Bahrami Children's Hospital (Tehran, Iran) in 2021 were enrolled. The patients underwent hematological and pulmonary function tests on the day of transfusion. Association between pulmonary function tests and demographic and laboratory data was investigated. Results: Spirometry indices including forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), and forced expiratory volume to forced vital capacity ratio (FEV1/FVC) were 86.14%±9.9, 87.86%±11.19, and 98.78%±10.97, respectively. In this study, the percentages of FEV1 and FEV1/FVC of patients older than 23 years were significantly lower compared to patients younger than 23 years. Moreover, a significantly lower FEV1/FVC ratio was seen in patients with higher body mass index and a serum ferritin level above 3,325 ng/dl. The most common impairment (19%) was a restrictive pattern. Conclusion: Age is inversely associated with FEV1 and FEV1/FVC ratio. Moreover, higher body mass index and serum ferritin levels are significantly associated with reduced FEV1/FVC ratio.